Development of an Equity, Diversity, and Inclusion Curriculum Initiative for Undergraduate STEM Students - Sim, Jenna A.P.; Jung, Mary E.; Chooniedass, Rishma; Eikenaar, Jannik Haruo (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
Equity, diversity, and inclusion (EDI) gaps persist in science, technology, engineering, and math (STEM) fields, as demonstrated by the discrimination, stereotyping, and inequities that historically and persistently marginalized groups face. Recognition of this gap led a transdisciplinary team to develop foundational-level e-learning modules, titled Foundations for Inclusive and Respectful Engagement (FIRE) on EDI capacities to be delivered in STEM undergraduate classes at the University of British Columbia’s Okanagan campus. FIRE consists of online, asynchronous, self-study modules delivered through the learning management system, Canvas. Feedback from pilot testing the FIRE modules has demonstrated that STEM students find the modules to be relevant and beneficial. Throughout the development of FIRE, we learned the importance of aligning the course with our institution’s values, working in a transdisciplinary team, and revising iteratively. This documentation of the development and preliminary feasibility of the FIRE modules aims to assist other institutions or organizations who are in the process of developing their own EDI teaching and learning materials.